Does Mastery of Goal Components Mediate the Relationship between Metacognition and Mathematical Modelling Competency? - Hidayat, Riyan; Zamri, Sharifah Norul Akmar Syed; Zulnaidi, Hutkemri (EDAM-Education Consultancy Limited, 2018)
Prior studies suggested close correlations among metacognition, mastery goal, and mathematical modelling competency. The present study examines the relationship between metacognition and mastery goal that may influence mathematical modelling competency. The current study employs 538 students of a mathematics education program; among these students, 483 (89.8%) are males and 55 (10.2%) are females, aged from 18 to 22 years old. The study follows a correlational research design to investigate and measure the degree of relationship among mathematical modelling competencies, mastery goal, and metacognition. Findings indicate that mastery goal positively affects mathematical modelling competency. SEM analysis indicates significant and positive influence of task-and self-approach goals on mathematical modelling competency, whereas task-avoidance goals are significantly and negatively related to mathematical modelling competency. By contrast, self-avoidance goals did not affect mathematical modelling competency. Task-approach goal is a positive partial mediator, task-avoidance goal is a negative partial mediator, self-approach goal is a positive full mediator, and self-avoidance goal is not a mediator between metacognition and mathematical modelling competency. In conclusion, metacognition positively affects the mathematical modelling competency of students, which is influenced by task-approach, task-avoidance, and self-approach goal but not self-avoidance goal.